Prospects and Challenges of the Chololo Pits Technology In Enhancing Crop Production in Semi-Arid Areas Of Central Tanzania: A Case Study of Chamwino District - Ismail, Zubeir; Kaswamila, Abiud; Maro, Fredy (Tanzania Journal for Population studies and Development, 2023)
This article explores the prospects and challenges affecting farmers practising the use of chololo pits[1] due to the semi-arid nature of Dodoma. It investigates the prospects and challenges of chololo pits technology in enhancing crop production in the semi-arid Chamwino District. Data was collected through documentary review, household interviews, focus group discussions, key informant interviews and field observation. Findings indicate that improvement of the soil water holding capacity (77.7%, n=337), economic use of fertilizers (74.4%, n=337) and increases in cereal yields (70.6%, n=337) were the major prospects for enhancing crop production. Labour intensity (43%, n=337), required skills (29%, n=337) and difficulty to maintain (13.5%, n=337) were the major challenges of chololo pits in enhancing crop production in the study area. Other minor prospects were reducing soil erosion, concentrating nutrients and protecting seeds and humus from being washed away, while shortage of fertilizer and waterlogging were the minor challenges of chololo pits. The study recommends that the government, in collaboration with NGOs and CBOs, should use more efficient tools to supplement the use of the hand-hoe (agriculture research institutions, COSTECH and SIDO should take lead on this). Also, further research should be conducted, and climate smart agriculture (CSA) and scaling up the chololo pits technology should be advocated.